Systemic activity of inhaled corticosteroid treatment in asthmatic children: corticotrophin releasing hormone test. Issue 3 (1st March 2003) - Pescollderungg, L; Radetti, G; Gottardi, E; Peroni, D G; Pietrobelli, A; Boner, A L
Abstract : Background: A study was undertaken to assess the function of the hypothalamic-pituitary-adrenal axis (HPA) in a group of asthmatic children before and after treatment with inhaled corticosteroids. Methods: Thirty prepubertal patients of mean (SD) age 6.7 (1.8) years were treated with inhaled corticosteroids. All children underwent a corticotrophin releasing hormone (CRH) test with evaluation of serum cortisol and adrenocorticotrophin hormone (ACTH) levels before and after 3 months of treatment. Twenty four hour urine samples were also collected to measure free cortisol (UFC) excretion. Results: Subjects showed no difference between basal serum cortisol levels (mean change –18; 95% CI –41 to 5; p=0.118) and delta (peak minus basal) levels (mean change –13; 95% CI –38 to 12; p=0.308) before and after treatment, whereas the peak cortisol level (mean change –31; 95% CI –55 to –7; p=0.013) and area under the curve (AUC) (mean change –175; 95% CI –288 to –63; p=0.003) after CRH were significantly lower following treatment. Basal, peak and AUC ACTH were significantly lower after treatment (p<0.05, p=0.004 and p=0.003, respectively), while delta ACTH was similar before and after treatment ((mean change –12; 95% CI – 31 to –7; p=0.199). No significant reduction in 24 hour UFC was observed after the treatment period (before 14.9 (7.1), after 15.0 (11.6); mean change 0.1, 95% CI –5.2 to 5.4; p=0.967). No correlation was found between UFC and any of the parameters of cortisol excretion following the CRH test, either before or after treatment. Conclusions: These data suggest that, at the dosage and for the treatment period used, inhaled steroids do not seem to suppress the HPA axis in the majority of patients. The CRH test may be more sensitive than 24 hour UFC and morning plasma cortisol levels in evaluating systemic activity of inhaled corticosteroid treatment.